Family Experience during Patient Assistance Process in General Intensive Care Unit: A Phenomenology Study - Safitri, Dwi; Kurnia, Anna; Al Jihad, Much (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Intensive care unit (ICU) treatment can lead to fear, anxiety, depression, panic, and tension in the family. Place of the family as active presence, guardian, facilitator, historian, and coaching of the family cannot be separated from the recovery process. During the assistance of ICU patients, the family is faced with a strange environment, strict rules, emotional stress, and everyday life changes that have caused them to encounter psychological and physiological concerns. AIM: This study aims to describe and interpret of the family’s experience during assistance patient in the ICU. METHODS: A phenomenological methodology is used to explore experience of family. In-depth interviews were conducted on nine participants who were selected using purposive sampling. Data were analyzed by Colaizzi techniques, began with read transcripts, look for phenomenon, formulated data, organized, and verified to the participants. RESULTS: The result is presented in three themes; physically and psychologically tired; good language is a medicine, strengthens each other’s companion. CONCLUSION: The support of the patient in the ICU helps the family face a number of stressful circumstances. Adaptive coping and psychosocial help from health care workers and friends build a supportive family to cope with the difficulties when supporting patients in the ICU.